2012
DOI: 10.1007/s11739-012-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index on intubation success rates and complications during emergency airway management

Abstract: We evaluated the effect of body mass index (BMI) on intubation success rates and complications during emergency airway management. We retrospectively analyzed an airway registry at an academic medical center. The primary outcomes were the incidence of difficult intubation and complication rates, stratified by BMI. We captured 1,075 (98 %, 1,075/1,102; 95 % CI 97-99) intubations. Four hundred twenty-six patients (40 %) had a normal BMI, 289 (27 %) were overweight, 261 (25 %) were obese, and 77 (7 %) were morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
1
33
1
2
Order By: Relevance
“…Colton House et al 20 found that weight does not appear to have a significant correlation with the incidence of laryngeal injury. Likewise, Dargin et al 25 concluded that body mass index was not predictive of postintubation complications. Interestingly, they also found that obesity, but not morbid obesity, predicted difficult intubation.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Colton House et al 20 found that weight does not appear to have a significant correlation with the incidence of laryngeal injury. Likewise, Dargin et al 25 concluded that body mass index was not predictive of postintubation complications. Interestingly, they also found that obesity, but not morbid obesity, predicted difficult intubation.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In one retrospective study in 1435 patients with trauma in the ED, there was no significant association between BMI and intubation failure, complications or death 15. Another investigation (n=1053) evaluated the effect of obesity and morbid obesity on the presence of a difficult airway, which was defined as the need for three or more intubation attempts 5. Interestingly, obesity predicted a difficult airway, but morbid obesity did not.…”
Section: Discussionmentioning
confidence: 99%
“…RSI is a technique involving the near simultaneous administration of an anaesthetic agent and a neuromuscular blocking agent (NMBA) to facilitate placement of an endotracheal tube 4. There is the potential that obesity could increase the difficulty of RSI 5. With increased difficulty, patients are more likely to require repeated attempts to place the endotracheal tube, which increases the risk of complications 6 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Some authors postulate that every obese patient can be considered as potentially difficult to intubate, regardless of the indicators. [11] Moreover, the literature reports that not all determinants are always good predictors. [5] There are some findings reporting that for example not only Mallampati classification but also the thyromental distance can produce false-positive results.…”
Section: Discussionmentioning
confidence: 99%